ENDODONTIC TREATMENT OF A LOWER RIGHT SECOND MOLAR WITH A "C"-SHAPED CANAL: CASE REPORT. (CIPEEX, 2025)
When faced with endodontic therapy, there are challenges to be faced, among which we can mention the internal root morphology and the presence of microorganisms in regions of difficult access. Several factors are decisive for the success of the treatment. Among them, the correct diagnosis, individualized planning and a careful sanitation process. The objective was to report a clinical case of endodontic treatment in a lower right second molar with a C-shaped canal. The patient came to the office reporting intense pain in the region of the right side of the mandible and through the clinical and radiographic data, the diagnosis of symptomatic pulpitis was made. When performing the coronary access, it was possible to visualize an isthmus connecting the mesiovestibular and distal canals, and the initial emptying of the canals and intracanal medication (UltraCal) were performed. A cone beam computed tomography exam was requested, confirming the unique C-shaped morphology. The operative steps involved odontometry, preparation of the root canals with an EasyLogic 40.05 rotary file, work in the isthmus region with an E2D ultrasonic insert, abundant sanitation using 2.5% sodium hypochlorite and an E1 ultrasonic insert, intracanal medication (UltraCal) and temporary sealing with glass ionomer cement. After 15 days, the patient returned asymptomatic and the sanitation protocol was performed again, obturation with calibrated cones (40.05) and BioCSealer cement and restoration with A2 light-cured composite resin. It is concluded that individualized planning associated with tomographic images allowed better knowledge of the atypical internal anatomy, enabling the execution of the surgical steps with caution and rigor, these factors being crucial to favor the success of endodontic treatment.
Keywords: molar tooth; anatomical variation; case report; cone beam computed tomography